2019
DOI: 10.1182/blood.2019000761
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of action of ruxolitinib in murine models of hemophagocytic lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is an often-fatal disorder characterized by the overactivation of T cells and macrophages that excessively produce proinflammatory cytokines, including interferon-γ (IFN-γ). Previously, we reported that the JAK inhibitor ruxolitinib dampens T-cell activation and lessens inflammation in a model of HLH in which perforin-deficient (Prf1−/−) mice are infected with lymphocytic choriomeningitis virus (LCMV). Ruxolitinib inhibits signaling downstream of IFN-γ, as well as sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 53 publications
13
91
0
1
Order By: Relevance
“…In line with a putative pathogenic role of IFNγ signaling, a high frequency of MAS was reported. The observation in our patient of (1) elevated frequency of Th1 cells, main producers of IFNγ3, and (2) a clinical response to ruxolitinib, blocking the IFNγ signalling, although not selectively,4 5 is consistent with this hypothesis. Although no definite conclusion can be drawn from this single case, our report suggests that ruxolitinib may represent a valid therapeutic option to be tested early in patients with s-AJI associated with severe early-onset lung disease.…”
supporting
confidence: 88%
“…In line with a putative pathogenic role of IFNγ signaling, a high frequency of MAS was reported. The observation in our patient of (1) elevated frequency of Th1 cells, main producers of IFNγ3, and (2) a clinical response to ruxolitinib, blocking the IFNγ signalling, although not selectively,4 5 is consistent with this hypothesis. Although no definite conclusion can be drawn from this single case, our report suggests that ruxolitinib may represent a valid therapeutic option to be tested early in patients with s-AJI associated with severe early-onset lung disease.…”
supporting
confidence: 88%
“…Beginning on day 4 after LCMV infection, we treated mice with vehicle, DEX, or DEX in combination with RUX at a dose that mediated a measurable reduction in pSTAT5 (supplemental Figure 2F). Consistent with prior reports, 15,25 all LCMV-infected vehicle-treated mice lost weight and died by 2 weeks postinfection ( Figure 4A-B). Although LCMV-infected mice treated with DEX exhibited slightly longer survival, all animals eventually succumbed to disease.…”
Section: Dex and Rux Function Cooperatively To Lessen Hyperinflammatisupporting
confidence: 92%
“…RUX also has the potential to inhibit the activity of cytokines that contribute to disease pathogenesis, but do not modulate DEX sensitivity, such as IFN-g. IFN-g did not promote DEX resistance in our model, but is currently under investigation as a therapeutic target in HLH. 25 Thus, our work, in conjunction with the established role for CD8 T cells as drivers of HLH, suggests that combining DEX and RUX has the dual potential to enhance DEX-induced apoptosis and attenuate other cytokine-mediated contributions to disease progression.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that the anti-IL-6R antibody tocilizumab has been beneficial in treating Chinese COVID-19 patients with CSS 17 . In addition, small molecule inhibitors of Janus kinases (JAK), such as the JAK1/2 inhibitor, ruxolitinib, are capable of blocking signaling downstream of IL-6, IFN-g, and other cytokines 18,19 . Thus there may be a variety of targeted cytokine inhibitors available that may benefit patients with COVID-19-induced CSS ( Table 2).…”
mentioning
confidence: 99%